Analysis of stresses during the polymerization shrinkage of self-curing resin cement in indirect restorations: A finite-element study - Tulimar M Cornacchia; Guilherme C Silva; Claudia S Magalhaes; Allyson N Moreira; Estevam B Las Casas (Wolters Kluwer Medknow Publications, 2014)
Background: Adhesive cementation is essential for the longevity of indirect esthetic restorations. However, polymerization shrinkage of resin cement generates stress, which may cause failures in the tooth-restoration interface. So, understanding of the biomechanics of resin cement is important for predicting the clinical behavior of an esthetic indirect restoration. Aims: To analyze the stresses generated during polymerization shrinkage of self-curing resin cement in ceramic and in indirect resin (IR) restorations, using the finite-element method (FEM). Settings and Design: Numerical study using the finite-element analysis. Materials and Methods: A three-dimensional (3D) model of a second molar restored with ceramic or IR onlay restoration was designed. The polymerization shrinkage of self-curing resin cement was simulated in FEM software using an analogy between the thermal stress and the resulting contraction of the resin cement. The localization and values of tensile stresses in the dental structure, cement, and adhesive layer were identified. Results: The location and value of the tensile stresses were similar for the two restorative materials. High tensile stresses were identified in the axiopulpal wall and angles of the tooth preparation, with the major stresses found in the cement located in the axiopulpal wall. Conclusions: The high stresses values and their concentration in the angles of the prepared tooth emphasize the importance of round angles and the use of cements with lower rates of shrinkage.